Resource Windfalls, Macroeconomic Stability and Growth : The Role of Political Institutions - Kazimov, Kazim (IMF Working Papers; Working Paper ;, 2011)
We use a new dataset on non-resource GDP to examine the performance of commodity-exporting countries in terms of macroeconomic stability and economic growth in a panel of up to 129 countries during the period 1970-2007. Our main findings are threefold. First, we find that overall government spending in commodity-exporting countries has been procyclical. Second, we find that resource windfalls initially crowd out non-resource GDP which then increases as a result of the fiscal expansion. Third, we find that in the long run resource windfalls have negative effects on non-resource sector GDP growth. Yet, the effects turn out to be statistically insignificant when controlling for government spending. Both the effects of resource windfalls on macroeconomic stability and economic growth are moderated by the quality of political institutions.